Pengaruh Tax Amnesty, Pemahaman Peraturan Perpajakan dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak pada KPP Pratama Pematang Siantar - Purba, Rophita Sonia; Dalimunthe, Hasbiana; Habibie, Muhammad (International Journal Labs, 2025)
This study aims to analyze the influence of tax amnesty, understanding of tax regulations, and tax sanctions on taxpayer compliance at the Primary Tax Office (KPP) Pratama Pematang Siantar. The sample in this study was 100 respondents who were registered taxpayers at the Pematang Siantar Pratama Tax Service Office. Sampling used random sampling with a significance level of 0.05. Taxpayer compliance is a crucial factor in optimizing state revenue through taxes. In recent years, the government has implemented various policies, such as tax amnesty, to increase taxpayer compliance. Understanding tax regulations and the existence of tax sanctions are also factors that can affect the level of taxpayer compliance. This study uses a quantitative approach with a survey method involving taxpayers registered at KPP Pratama Pematang Siantar as respondents. The data were analyzed using multiple linear regression to examine the relationship between the studied variables. The results show that tax amnesty and understanding of tax regulations have a positive and significant influence on taxpayer compliance. Meanwhile, tax sanctions also affect compliance but with a lower level of significance compared to the other two variables. These findings indicate that increasing understanding of tax regulations and effective tax amnesty policies can enhance taxpayer compliance. Therefore, further efforts from tax authorities are needed to improve tax education and implement more effective sanctions to encourage taxpayer compliance.